A welfare comparison between export subsidies and exchange rate depreciation - Adelina Gschwandtner (Institute for Advanced Studies (IHS), 1999)
This paper develops a Bertrand Price Competition model with differentiated goods in which export subsidies are compared to exchange rate depreciation as different government policies for promoting exports. National governments may wish to help domestic firms to expand market shares in profitable areas and might do this through either one of these two tools. Their effects on equilibrium values are analyzed and compared. It is shown that while the two examined trade policies give rise to the same highest welfare, they could produce some significant differences according to circumstances. If the exchange rate is sufficiently high and the level of the nominal wage sufficiently low, the marginal effect of the subsidy will be higher. But if unions are strong (and demand a high nominal wage) and the exchange rate is sufficiently low, the governments could also consider a depreciation as an alternative policy to export subsidies.
Keywords: F13; F31; 330; export subsidies; exchange rate depreciation; international trade; Bertrand competition; Exportsubvention; Abwertung; Außenhandelsförderung; Wohlfahrtsanalyse; Preiswettbewerb; Wirkungsanalyse; Theorie